Crystal structure of poly[bis[μ3-1,3,5-tris[(1H-imidazol-1-yl)methyl]benzene-κ3N:N′:N″]nickel(II)] hexafluorosilicate, C36H36N12NiSiF6 - Xu Xi‐Ting; Dong Tong‐Min; Song Wei; Zhong Kai‐Long (Zeitschrift für Kristallographie - New Crystal Structures)
C36H36N12NiSiF6, trigonal, P3‾$P‾{3}$ (no. 147), a = 9.5965(3) Å, c = 11.8821(8) Å, V = 947.65(9) Å3, Z = 1, Rgt(F) = 0.0437, wRref(F2) = 0.1076, T = 223 K.